2001
DOI: 10.1071/zo00078
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism (RFLP) analysis of three nuclear genes in rock-wallabies (Petrogale: Marsupialia: Macropodidae): a search for genic markers to identify taxa within the Petrogale lateralis-penicillata group

Abstract: Many rock-wallaby (Petrogale) species within the lateralis–penicillata complex are morphologically similar and can be distinguished only by their unique karyotypes, frustrating attempts to identify specimens in the field and in museums. As chromosome preparations are not always obtainable from specimens, additional diagnostic molecular markers are required. In this study, restriction fragment length polymorphism (RFLP) analysis of three nuclear genes was undertaken using 100 Petrogale specimens, including repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous attempts to identify unknown taxa using traditional morphological criteria have sometimes been challenging when dealing with morphologically cryptic species such as Petrogale (Loupis and Eldridge 2001). Other researchers have shown that although karyotypes can be useful in differentiating rock-wallaby taxa (Eldridge et al 1991a), a major limitation is the necessity of living tissue that can then be cultured (Eldridge and Spencer 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to identify unknown taxa using traditional morphological criteria have sometimes been challenging when dealing with morphologically cryptic species such as Petrogale (Loupis and Eldridge 2001). Other researchers have shown that although karyotypes can be useful in differentiating rock-wallaby taxa (Eldridge et al 1991a), a major limitation is the necessity of living tissue that can then be cultured (Eldridge and Spencer 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to DNA studies one of the most convincing genetic species determiners had been chromosome and allozyme similarities (Sharman et al 1989;Eldridge et al 1991aEldridge et al , 1991bEldridge et al , 1994. However, the use of chromosomes to provide definitive species identification is limited by the technique's requirement for living tissue from which rapidly dividing cells can be cultured for analyses (Eldridge and Spencer 1997;Loupis and Eldridge 2001). Now with DNA studies becoming a diagnostic tool for species identification, it is mandatory that this research be used in identifying which subspecies/races of P. lateralis likely occurred on DI.…”
Section: Introductionmentioning
confidence: 99%